If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying rt = rk Solving rt = kr Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1kr' to each side of the equation. -1kr + rt = kr + -1kr Combine like terms: kr + -1kr = 0 -1kr + rt = 0 Factor out the Greatest Common Factor (GCF), 'r'. r(-1k + t) = 0Subproblem 1
Set the factor 'r' equal to zero and attempt to solve: Simplifying r = 0 Solving r = 0 Move all terms containing r to the left, all other terms to the right. Simplifying r = 0Subproblem 2
Set the factor '(-1k + t)' equal to zero and attempt to solve: Simplifying -1k + t = 0 Solving -1k + t = 0 Move all terms containing r to the left, all other terms to the right. Add 'k' to each side of the equation. -1k + k + t = 0 + k Combine like terms: -1k + k = 0 0 + t = 0 + k t = 0 + k Remove the zero: t = k Add '-1t' to each side of the equation. t + -1t = k + -1t Combine like terms: t + -1t = 0 0 = k + -1t Simplifying 0 = k + -1t The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
r = {0}
| (4/x)+2-(3/2)=0 | | -255=3x-7(3x+21) | | 63-4x=5x+19 | | y^2+14y-15=0 | | 18h=63 | | 4(-7k-7)=84 | | 74-5x=4x+23 | | 4q^2+3q=3q^2-4g+18 | | (-42*-6+40)=15(-8*-6+244) | | -7x-1(-2x-2)=27 | | 123=-7x+5(5x-15) | | (15/8)z+(1/4)-4 | | 2y^2-7y-13=-10 | | (-42x+40)=15(-8x+244) | | (-42+40)=15(-8x+244) | | -281=-6x+7(-3x-17) | | 5(7-2y)+9y=31 | | (3R/4)-(4/5)=(7/10) | | 15=4x-7(x-6) | | 18-(14+f)=1-(4f+6) | | 6x+5(-5x+13)=-68 | | -2-6x=4x+12 | | -260=-3x-5(-6+25) | | 15x+20=5x+200 | | 10-x-x=24 | | 6(2c-7)+16=2(4c-1)+8 | | 8*4n-1= | | -68=-4x+5(-x-8) | | 5x+6+8x=5+8x-3x-20-3 | | 3x+25-100=0 | | 60q+45r+75s-180=15(4q+3r+5s+11) | | -68=-4x+5 |